Indicators of a Cardiovascular System at 14-15 Years Old Boys at Short-term Biofeedback Training for Controlling of General Heart Rate Variability After Speed and Power Training: Experimental Controlled Study - Liliya V. Poskotinova; Olga V. Krivonogova; Oleg S. Zaborsky ("Paediatrician" Publishers LLC, 2019)
Background. Cardiovascular system recovery after physical activity with explosive exercises is essential for cardiovascular pathology prevention. The efficiency of short-term biofeedback training (BFB training) in such conditions in adolescents have not been studied earlier. Objective. Our aim was to study the effect of BFB training on cardiovascular rehabilitation after speed and power training in adolescents according to general heart rate variability (HRV) spectrum total power parameter. Methods. The research has included healthy eighth-grade students (14-15 years old boys) from regular school. Inclusion in experimental and control groups was regulated by researches. Such indicators as total power (TP) of HRV spectrum, tension index (TI), systolic and diastolic arterial blood pressure (ABP), heart rate (HR) were registered initially, after three standing long jumps with double take-off and after recovery. All members of experimental group performed BFB training in order to increase TP (3 min) during recovery period. Members of control group were resting. Results. Initially all members of experimental (n = 17) and control (n = 10) groups were compared on age, height, weight and TP, TI, ABP and HR indicators. The TP level in boys of experimental group was higher than in control group during recovery period after BFB training: 3.22 (1.96; 6.13) against 1.36 (1.15; 1.84) X 1000 ms2 respectively (р = 0.041). There were no differences in TI, ABP and HR levels between two groups during recovery period. Conclusion. Implementation of short-term BFB training according to general HRV spectrum total power parameter in 14-15 years old boys after speed and power training perpetuates vagal impact on heart rate during recovery period.